Pengaruh Teknologi Digital terhadap Perkembangan Ekonomi dalam Industri Pariwisata - furqan; Manurung, Sabam Syahputra (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Digital technology has become one of the important factors in economic development in the tourism industry. This study aims to analyze the influence of digital technology on economic development in the tourism industry. The results show that digital technology has a significant influence on economic development in the tourism industry, especially in improving accessibility, promotion, income, and service quality. However, the use of digital technology also has several challenges that need to be overcome, such as dependence on technology, lack of human resources, and lack of security. Therefore, it is necessary to conduct further research to find out how digital technology can be used effectively and efficiently in the tourism industry.